2014
DOI: 10.1161/jaha.114.001197
|View full text |Cite|
|
Sign up to set email alerts
|

National Trends in Recurrent AMI Hospitalizations 1 Year After Acute Myocardial Infarction in Medicare Beneficiaries: 1999–2010

Abstract: BackgroundThere are few data characterizing temporal changes in hospitalization for recurrent acute myocardial infarction (AMI) after AMI.Methods and ResultsUsing a national sample of 2 305 441 Medicare beneficiaries hospitalized for AMI from 1999 to 2010, we evaluated changes in the incidence of 1‐year recurrent AMI hospitalization and mortality using Cox proportional hazards models. The observed recurrent AMI hospitalization rate declined from 12.1% (95% CI 11.9 to 12.2) in 1999 to 8.9% (95% CI 8.8 to 9.1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
2
40
1
1
Order By: Relevance
“…In some studies, HIV-positive individuals have previously been found to have a higher rate of recurrent MIs and to more frequently undergo urgent angioplasties [18,28,35,36,37]. The proportion of recurrent MIs in the study was 11.6%; which is higher compared with previous findings from the general population (8.9% in 2010) [38]. We were unable to systematically evaluate the type of MI and degree of vessel disease, but the relatively young median age of the study participants at the time of MI may indicate that a higher proportion may have had a ST-elevated myocardial infarction (STEMI), as an inverse relationship has been demonstrated in men in the general population between age and the likelihood of the MI being a STEMI [39].…”
Section: Discussioncontrasting
confidence: 60%
“…In some studies, HIV-positive individuals have previously been found to have a higher rate of recurrent MIs and to more frequently undergo urgent angioplasties [18,28,35,36,37]. The proportion of recurrent MIs in the study was 11.6%; which is higher compared with previous findings from the general population (8.9% in 2010) [38]. We were unable to systematically evaluate the type of MI and degree of vessel disease, but the relatively young median age of the study participants at the time of MI may indicate that a higher proportion may have had a ST-elevated myocardial infarction (STEMI), as an inverse relationship has been demonstrated in men in the general population between age and the likelihood of the MI being a STEMI [39].…”
Section: Discussioncontrasting
confidence: 60%
“…These high all‐cause death rates may reflect the advanced age, history of CVD, and prevalence of comorbid conditions in the study population and are relatively consistent with other studies in similar populations. For example, 1‐year all‐cause mortality rates (2010) for Medicare patients who experienced a recurrent MI or stroke within 1 year of hospitalization for MI were 30% for patients with recurrent MI, 35% for those with IS following MI, and 61% for those with hemorrhagic stroke following MI . In another study of MI survivors at least 65 years old who subsequently died within 3 years of follow‐up, >50% of the deaths were attributed specifically to CVD .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these across-the-board improvements, the proportional decline in recurrent AMI rehospitalization was larger in whites (27.7%) than in blacks (13.6%), so that at the end of the study period, the discrepancy between whites and blacks had actually increased. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Longer than whites More likely than whites More likely than whites Door-to-drug times 12 Prescribed aspirin 5 Survive and be discharged (when not treated with revascularization) 3 Door-to-balloon times 12 Rehospitalization (nonwhites) 11 More likely than whites Less likely than whites Recurrent AMI (nonwhites) 11 Slower transfer to revascularization hospital 14 Diagnostic cardiac catheterization 5 Recurrent AMI (5 years post-PCI) 32 Less likely than whites Catheterization 31,33 Rehospitalized for AMI (<1 year post-AMI) 18 Door-to-balloon times <90 minutes 13 Non-protocol mandated angiography (nonwhites) 11 Death (nonwhites) 11 Transfer to hospital with revascularization services 15 Use of lidocaine 6 Death following CABG (nonwhites) 28 PCI 5,7 Mortality (>30 days post-AMI) 15 PCI or CABG within 3 months of AMI 17 Mortality (5 years post-PCI) 32 Revascularization (admitted to nonrevascularization hospital) 15 Rehospitalization or death within 1 year post-CHD hospitalization 30 Revascularization 3,16,34 Adverse cardiac outcomes (1-year post revascularization) 35 6 Receive stent if undergoing PCI (nonwhites) 11 Less likely than whites Stress test 33 Procedural success with PCI (nonwhites) 11 Echocardiogram 33 Mortality <30 days post-AMI 15 Drug-eluting stents 4 Prescribed prasugrel 4 Prescribed clopidogrel 5 Prescribed GP IIb/IIIa inhibit...…”
Section: Delays Treatments Outcomesmentioning
confidence: 99%